Análise de vibrações induzidas por vórtices (VIV) em risers de perfuração - Matala, Aaron Amono (2018)
Offshore drilling risers, which are tubular connecting structures between wells and floating units, are affected by the increase in water depth due to the low relation between their diameters and total lengths. The occurrence of Vortex Induced Vibrations (VIV) in these structures is a phenomenon that can cause problems in their functioning and productivity and can even cause the fatigue rupture of these structures. During operation, these Risers are subjected to high static and dynamic loads. In this scenario, the present work presents results of the contribution of some parameters of the VIV analysis in the fatigue resistance of a drilling Riser, considering its whole length. Thus, the determination of the critical point for fatigue prediction considering the Riser / BOP / Well model as well as the understanding of the behavior of the developed models and are sought. Possible improvements of the model are also indicated.